Decision support for sustainable urban mobility: A case study of the Rhine-Ruhr area. (May 2022) - Melkonyan, Ani; Gruchmann, Tim; Lohmar, Fabian; Bleischwitz, Raimund
Highlights: A framework for integrated innovation policy of sustainable urban mobility is set. A multi-actor and multi-level approach is considered. Transformation process is step-wise guided. An interactive scenario-simulation tool for the decision makers is developed. Mobility demand and supply must be balanced to transform sustainable urban future. Abstract: Sustainable urban governance considers the simultaneous reduction of traffic-related pollution, social equity for mobility access, healthy market competition among the service providers, and convenient use of multi-modal transportation enabled by digital technologies. However, the rise of more complex urban systems challenges decision-making processes to design and implement environmentally sustainable, economically viable, and socially acceptable urban mobility systems. The paper sets an innovative and collaborative decision-making framework for integrated sustainable urban policy design. Firstly, schematic integration of urban flows from disintegrated operation systems toward fully integrated, inclusive, and sustainable urban systems is conceptualized. Based on this concept a multi-level decision-making process within urban mobility policies is designed relying on a Multi-Criteria Decision Aid (MCDA) for resource allocation decisions at the micro, meso, and macro levels. Thereby, a range of urban futures is adequately addressed, be it smart, sustainable city concepts, peri-urbanization, and business as usual scenarios. The integrated model for a pilot case of the metropolitan region of Rhine-Ruhr is tested in this paper. If Sustainable City scenario is the desired one, push and pull measures should be equally weighted. Based on MCDA sensitivity analysis, policy recommendations and a practical hands-on tool for urban planning are derived.